2003
DOI: 10.1038/sj.bjp.0705188
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin upregulates the activity of phagocytosis through 5‐HT1A receptors

Abstract: 1 In this study, we investigated whether serotonin could regulate the in vitro activity of phagocytosis through 5-hydroxytryptamine or serotonin (5-HT 1A ) receptors. 2 Mouse peritoneal macrophages were cultured with serotonin and the activity of phagocytosis was assessed by the uptake of zymosan and latex particles added to the culture media. Specific binding of [ 3 H]8-OH-DPAT and immunohistochemistry using an affinity-purified anti-5-HT 1A -receptor antibody were assayed in the macrophages. In addition, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 28 publications
(28 reference statements)
0
52
0
Order By: Relevance
“…For example in macrophages, 5-HT stimulates phagocytosis 67 of cells that contained zymosan, a component of yeast cell walls that is used to induced sterile inflammation. 68 5-HT also plays a role in enhancing the cytotoxicity of NK cells 67,69 cells in blood and lymph that are not phagocytic but promote cell lysis when stimulated. Together, these findings indicate that multiple cells of the native immune system possess the machinery to produce, store, release, and respond to 5-HT, with the overall picture being one to mobilize cells to target to, and destroy, pathogens.…”
Section: Targets In the Peripheral Immune Systemmentioning
confidence: 99%
“…For example in macrophages, 5-HT stimulates phagocytosis 67 of cells that contained zymosan, a component of yeast cell walls that is used to induced sterile inflammation. 68 5-HT also plays a role in enhancing the cytotoxicity of NK cells 67,69 cells in blood and lymph that are not phagocytic but promote cell lysis when stimulated. Together, these findings indicate that multiple cells of the native immune system possess the machinery to produce, store, release, and respond to 5-HT, with the overall picture being one to mobilize cells to target to, and destroy, pathogens.…”
Section: Targets In the Peripheral Immune Systemmentioning
confidence: 99%
“…21 The peritoneal macrophages were cultured for 24 hours, and Cy5.5 (Molecular Probes)-labeled zymosan was added to the macrophages for an hour in a final concentration of 100 g/ml. The number of zymosan particles in a cell was quantitatively determined.…”
Section: Phagocytosismentioning
confidence: 99%
“…They found that 5-HT enhanced latex bead ingestion when cells were simultaneously exposed to small concentrations of IFN␥ but inhibited ingestion when exposed to larger concentrations. In contrast, Freire-Garabal et al (42) found that a short exposure to 5-HT increased latex bead phagocytosis by resident peritoneal macrophages from BALB/c mice. More recently Krabbe et al (43) demonstrated that 5-HT inhibits ingestion of microspheres by microglia, resident macrophages of the CNS.…”
Section: Discussionmentioning
confidence: 85%
“…Several groups have studied the effect of 5-HT on phagocytosis of targets that are unrelated to efferocytosis by murine peritoneal macrophages, such as bone marrow-derived macrophages and microglia, but the effects have been variable (42)(43)(44). We performed similar experiments using resident and TGelicited peritoneal macrophages and found that 5-HT inhibited ingestion of latex beads, but had no effect on ingestion of IgGopsonized erythrocytes through the Fc␥ receptor (Fig.…”
Section: Effect Of 5-ht On Efferocytosis-mentioning
confidence: 99%